Transformers, EarthSpark. Season 1, episodes 1-10 [videorecording (DVD)] - Malinowski, Dale; Ward, Ant (Anthony); Dubuc, Nicole, 1978- (Paramount, 2023)
The Transformers' War on Earth ended years ago. Dot Malto, a veteran of the war, along with her husband, Alex, and their kids, Robby and Mo, move to the remote town of Witwicky, Pennsylvania, to start a new life. But Witwicky proves to be more than meets the eye and the family soon finds their lives intertwined with the Terrans, Twitch and Thrash, the first generation of Transformers robots to be born on Earth! When the evil half human/half robot cyborg Dr. Meridian (aka MANDROID) threatens life as they know it, Robby, Mo, and the Terrans band together with legendary Autobots like Optimus Prime and Bumblebee to stop Mandroid once and for all!